The financial risk of local government units from the perspective of commercial banks - Gubernat, Ewa (Ryzyko finansowania jednostek samorządu terytorialnego w ocenie banków komercyjnych, 2015)
Local government units carry out tasks aimed at meeting the needs of the local community. The implementation of these tasks necessitates the collection and disbursement of funds. As practice shows, rarely is a balance reached between revenue and expenditure. The shortage of the necessary funds to cover all planned expenditures in a given year causing the budget deficit, which in turn causes the need for borrowing. On this specific issue, this article presents the current scope of local government co-operation with banks. The article presents a catalogue of loan products and their availability to local governments. In this respect, the author has paid particular attention to the range of analyzed banks’ risks, and the availability of information about the risks. This in the fullest possible way supports the implementation of the lending process, especially in terms of long-term financing. The primary purpose of the considerations made in this study was to find answers to the questions: what kind of risks are analyzed by banks in the lending process and how relevant are they? The conclusions were based on a literature review and survey research concerning the co-operation between commercial banks with local government units
Nauki o Finansach = Financial Sciences, 2015, Nr 4 (25), s. 39-50
Keywords: risk; local government; bank; ryzyko; samorząd